PENGARUH PENGGUNAAN METODE PENGAKUAN PENDAPATAN TERHADAP PENETAPAN BESARNYA LABA PADA PT. PLN (PERSERO) AREA PELAYANAN DAN JARINGAN CIMAHI JAWA BARAT - dewi endah fajarina (STKIP PGRI TULUNGAGUNG, 2018)
Abstrack: Every company needs an accurate accounting information to determine the policies that will be the company to get an accurate accounting information required careful recording of transactions, can be accounted for, and in accordance with accepted accounting principles in Indonesia. PT PLN (Persero) and Network Service Area Cimahi as a business entityorlimited company requires an accurate accounting information erived from transaction records that can be accounted for, for the purposes of the Income Method of recording required. Accountable and profitable for the company because it is necessary for the calculation of the financial statements with Revenue Recognition Methods. From these calculations is expected to obtain a revenue recognition method which is really beneficial for the company. The method used is an associative analysis method that aims to find there a causal influence of one variable with another variable, which is cause and effect. The study population is the data related to the company's revenue, the data collected through observation and interviews document study. Taking into account the results of this study concluded that PT PLN (Persero) Revenue Recognition Method using the Accrual Basis and have been implemented in accordance with accepted accounting principles in Indonesia. Goodness Accrual Basis method is able to record income and expenses received in advance or accrued. While the influence of the method of determining the amount of revenue recognition profit amounted to 0,998. Furthermore, a significant difference between the recognition of revenue and the profits that t = 20.768 t consulted with a 5% error table to test the two parties and df (degrees of freedom) = (n-2) = 2, in order to obtain the t table = 4.303 means that t is greater than t table (20.768 4.303). This condition allows the financial statements prepared in accordance with the actual conditions of the company and with accurate data. To maintain the accuracy of accounting records, it is advisable totighteninternal controls in accord an cewith the applicable provisions in accounting.